2020
DOI: 10.1136/vetreco-2019-000389
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Suissano Health Programme on antimicrobial usage on 291 pig farms in Switzerland

Abstract: BackgroundIn 2015, in Switzerland the Suissano Health Programme was implemented in pig production to improve transparency for antimicrobial usage (AMU) and to reduce the usage of fluoroquinolones (FQ), macrolides and cephalosporins, representing highest priority critically important antimicrobials.MethodsIn the presented cohort study, the impact of the Suissano programme on the AMU of 291 pig farms between 2016 and 2017 was investigated. AMU was calculated in total numbers of defined course doses (nDCDch) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…This study shows that for HPCIAs, the calculated number of defined daily doses was 21% of the overall consumption. Similar results with similar measuring methods have already been shown in earlier studies, which could also demonstrate the potential for reduction over time ( 10 , 39 ). Similarly to the deviations observed for the different age categories, the lower percentage of 7% HPCIAs measured as active ingredients shows the differences in output between the two measurement methods of defined daily doses and amount of active ingredients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study shows that for HPCIAs, the calculated number of defined daily doses was 21% of the overall consumption. Similar results with similar measuring methods have already been shown in earlier studies, which could also demonstrate the potential for reduction over time ( 10 , 39 ). Similarly to the deviations observed for the different age categories, the lower percentage of 7% HPCIAs measured as active ingredients shows the differences in output between the two measurement methods of defined daily doses and amount of active ingredients.…”
Section: Discussionsupporting
confidence: 90%
“…This might result in a selection bias in the study population and could compromise the internal validity of the analyses in this study. Although participation in the program is without benchmarking or consequences, a reduction of AMU on farms could be observed as a result of the comparison to other farms ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that HPCIAs represented 2.6 % of the global TI usage. This percentage is lower than in 2017 (3.6 %) and 2016 (4.2 %) [7]. Nevertheless, this does not mean that the quantity of HPCIAs used in 2020 is significantly lower, because the indicators used in both studies to quantify AMU are different [17][18].…”
Section: Discussionmentioning
confidence: 99%
“…This AMU monitoring system is coupled with the Health Programmes of the Swiss Pig Health Service of SUISAG and Qualiporc. One of the main objectives of the programme is to foster prudent use of antimicrobials and to increase transparency [7]. The number of farms participating in this programme is steadily increasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation